Optimizing Intellectual Property as a Fiduciary Security Object After the Issuance of Governmental Regulation No. 24 of 2022 - Jafar, Faisal Herisetiawan; Akbar, Muhamad Aksan; Sakti, La Ode Awal (Faculty of Law, Universitas Negeri Semarang, 2023)
The issuance of Governmental Regulation no. 24 of 2022 on the Executory Regulation of Law no. 24 of 2019 on Creative Economy has become a zephyr for creative economy actors with regard to intellectual property-collateralized financing schemes for their businesses. The regulation also further reinforces intellectual property ownership as a standalone fiduciary object that should no longer be viewed as supplementary collateral. This paper aims to study the optimization of governmental regulation on the creative economy with respect to intellectual property-collateralized financing. To this end, a normative legal method was applied by focusing on the secondary data. The research topic was scrutinized following the prevailing regulation and relevant literature. With the issuance of Governmental Regulation no. 24 of 2022 Creative Economy, it further strengthens the ownership status of intellectual property rights as objects of material guarantees. Every citizen, especially creative economy actors, can apply for business capital loans, which can be used as collateral objects and can be classified in the form of intellectual property which must be registered or registered with the Director General of Intellectual Property, Ministry of Law and Human Rights. This consequence has an impact on the establishment of an intellectual property appraisal institution that has the task of evaluating intellectual property that will be used as collateral.